Tumefactive Primary Central Nervous System Vasculitis: Imaging Findings of a Rare and Underrecognized Neuroinflammatory Disease - Suthiphosuwan, S.; Bharatha, A.; Hsu, C.C.-T.; Lin, A.W.; Maloney, J.A.; Munoz, D.G.; Palmer, C.A.; Osborn, A.G. (American Journal of Neuroradiology, 2020)
SUMMARY: Primary central nervous system vasculitis (PCNSV) is a poorly understood neuroinflammatory disease of the CNS affecting the intracranial vasculature. Although PCNSV classically manifests as a multifocal beaded narrowing of the intracranial vessels, some patients may not have angiographic abnormalities. A rare subset of patients with PCNSV present with masslike brain lesions mimicking a neoplasm. In this article, we retrospectively review 10 biopsy-confirmed cases of tumefactive PCNSV (t-PCNSV). All cases of t-PCNSV in our series that underwent CTA or MRA were found to have normal large and medium-sized vessels. T-PCNSV had a variable MR imaging appearance with most cases showing cortical/subcortical enhancing masslike lesion (70%), often with microhemorrhages (80%). Diffusion restriction was absent in all lesions. In summary, normal vascular imaging does not exclude the diagnosis of t-PCNSV. Advanced imaging techniques including MR perfusion and MR spectroscopy failed to demonstrate specific findings for t-PCNSV but assisted in excluding neoplasm in the differential diagnosis. Biopsy remains mandatory for definitive diagnosis.PCNSVprimary central nervous system vasculitist-PCNSVtumefactive PCNSVABRAamyloidβ–associated angiitisCAA-RIcerebral amyloid angiopathy–related inflammationESRerythrocyte sedimentation rateMRPMR perfusionCRPC-reactive proteinPCRpolymerase chain reactionVWIvessel wall imagingPCNSLprimary CNS lymphoma